Risk of tuberculosis is increased in Behcet's disease compared to other rheumatological disorders after anti-TNF alpha treatments: a case series and review of the literature - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2021)
Background/aim: Tumor necrosis factor-alfa (TNF-a) antagonists are extensively utilized in the treatment of inflammatory rheumatic diseases and also shown to be effective in Behcet's disease (BD) patients with major organ involvement. In this study, we aimed to re-evaluate the incidence of tuberculosis (TB) infection after anti-TNFa treatments and to reveal the risk of TB in BD. Methods: Data of patients who received anti-TNFa treatment between 2005 and 2018 were assessed retrospectively. Demographic features, TNF-a antagonist type/treatment time, tuberculosis skin test (TST) and QuantiFERON results, isoniazid prophylaxis status, and concomitant corticosteroid (CS) treatments were collected. Results: A total of 1277 (male/female = 597/680; median age = 49 years) patients were treated with TNF-a antagonist for a median of 33 months (Q1:12, Q3:62). Thirteen (1%) patients developed TB during the follow-up period. Within 13 TB-positive patients, 7 of them had pulmonary, and 7 had extrapulmonary TB. Although, the median time of (month) TNF-a antagonist treatment was higher in TB-positive patients than negative ones, the difference was not statistically significant (48 and 33 months, respectively, p = 0.47). Similarly, TB-positive patients were treated with CSs more than TB-negative patients (80% vs. 60%). Time from the initiation of TNF-a antagonist treatment to the diagnosis of TB had a median of 40 months (Q1-Q3: 22-56). There was a statistically significant increase of TB development in BD patients than non-BD patients after TNF-a antagonists (7.5% vs. 0.8%, respectively, p = 0.007). When we combined our patients with the other series from Turkey, among 12928 patients who received TNF-a antagonists, TB was positive in 12 (3.9%) of 305 BD patients compared to 112 (0.9%) of 12623 non-BD patients (p < 0.00001). Conclusion: Our results suggest a higher frequency of TB infections in BD patients with TNF-a antagonists. As biologic agents are increasingly used for major organ involvement in current practice for BD, screening mechanisms should be carefully implemented.
Keywords: Behcet's disease; TNF-a antagonists; tuberculosis; RHEUMATOID-ARTHRITIS; THERAPY; SUSCEPTIBILITY; INHIBITORS; PATIENT